Naturalism in American fiction : the classic phase - Conder, John J. (The University Press of Kentucky, 1984)
In this closely reasoned study, John J. Conder has created a new and more vital understanding of naturalism in American literature. Moving from the Hobbesian dilemma between causation and free will down through Bergson's concept of dual selves, Conder defines a view of determinism so rich in possibilities that it can serve as the inspiration of literary works of astonishing variety and unite them in a single, though developing, naturalistic tradition in American letters. At the heart of this book, beyond its philosophic discussion, is Conder's reading of key works in the naturalistic canon, beg.